The Importance of writing in English Language Classes - Abdurakhmonova Makhfuza Olimovna (Global Scientific Publishing, 2023)
Writing is a complex language skill. It allows using a system of graphic signs to ensure communication between people. This is a productive activity in which a person records speech for transmission to others. The formation of writing skills is especially important when teaching students a foreign language in primary school. The formation of writing skills in students plays an important role in the formation of other abilities, literacy, reading, listening, and speaking skills. This article discusses the importance of teaching writing to schoolchildren in the educational process.
Keywords: teaching; which; formation; educational